EFFICACY OF CRESTAR, PGF2a and GnRH COMBINATION iN · TREATMENT OF POST PARTUM ANESTROUS BUFFALOES - UTAG, S G; RAGHUWANSHI, D S; VOHRA, S C; KHAN, LA; SAHATPURE, S K (The Indian Journal of Animal Reproduction, 2023)
Twelve postpartum anestrous buffaloes were divided Into two equal groups. Group I was treatedwith Crestar ear implant + PGF 2• + GnRH for induction of estrus. Group II served as untreated C?ntrol.In group I, estrus was induced in 100% (n=6) treated buffaloes with an average duration of 42.38±11.09hrs Ovulation occurred in 83.33% (n=5) buffaloes of which three conceived. None of the buffaloes fromcontrol group exhibited estrus during experimental period. Intensity and the duration of induced estruswas also studied.
Keywords: Anestrous buffaloes; Crestar, PGF2alpha; GnRH; Efficacy